2017
DOI: 10.1007/s10886-017-0884-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet in Shaping the Chemical Signal Design of Lacertid Lizards

Abstract: Lizards communicate with others via chemical signals, the composition of which may vary among species. Although the selective pressures and constraints affecting chemical signal diversity at the species level remain poorly understood, the possible role of diet has been largely neglected. The chemical signals of many lizards originate from the femoral glands that exude a mixture of semiochemicals, and may be used in a variety of contexts. We analyzed the lipophilic fraction of the glandular secretions of 45 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…In addition, while climate (Baeckens, Martín, García‐Roa, Pafilis, et al, 2018; Martín, Ortega, & López, 2015) and diet (Baeckens, García‐Roa, et al, 2017; García‐Roa et al, 2017; Kopena et al, 2011) can affect lizard chemical signal design, our preliminary data suggest these factors are unlikely drivers of the observed divergence between the source and islet populations. As the source population was peninsular and at sea level, and due to the close physical proximity of the source and experimental populations (maximum linear distance of 28 km), all of the populations experience comparable temperature, precipitation and wind (Belasen et al, 2017; Table S6).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, while climate (Baeckens, Martín, García‐Roa, Pafilis, et al, 2018; Martín, Ortega, & López, 2015) and diet (Baeckens, García‐Roa, et al, 2017; García‐Roa et al, 2017; Kopena et al, 2011) can affect lizard chemical signal design, our preliminary data suggest these factors are unlikely drivers of the observed divergence between the source and islet populations. As the source population was peninsular and at sea level, and due to the close physical proximity of the source and experimental populations (maximum linear distance of 28 km), all of the populations experience comparable temperature, precipitation and wind (Belasen et al, 2017; Table S6).…”
Section: Discussionmentioning
confidence: 71%
“…Prior to any statistical analyses, proportion data was arcsin transformed (Baeckens, García‐Roa, Martín, & Van Damme, 2017; Baeckens, Martín, García‐Roa, Pafilis, et al, 2018; Baeckens, Martín, García‐Roa, & Van Damme, 2018; Sokal & Rohlf, 1995). Alternative transformations, such as the compositional analysis for proportions (Aebischer, Robertson, & Kenward, 1993), provided similar results.…”
Section: Methodsmentioning
confidence: 99%
“…Future work could usefully investigate other visual signals and chemical signals to determine whether factors other than body shape may also contribute the decision process of T. septentrionalis . It has been found that Takydromus lizards among species having the visual [ 51 ] and chemical [ 52 55 ] communication systems and abilities to signal with conspecifics and alter their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could usefully investigate other visual signals and chemical signals to determine whether factors other than body shape may also contribute the decision process of T. septentrionalis. It has been found that Takydromus lizards among species having the visual [51] and chemical [52][53][54][55] The body posture of heterospeci c (a, between male T. septentrionalis and female T. sexlineatus) and conspeci c homosexual (b, between males of T. septentrionalis) mating partners.…”
Section: Discussionmentioning
confidence: 99%